Suppression of epileptic seizures by transcranial activation of K+-selective channelrhodopsin - Xiaodong Duan; Chong Zhang; Yujie Wu; Jun Ju; Zhe Xu; Xuanyi Li; Yao Liu; Schugofa Ohdah; Oana M. Constantin; Yifan Pan; Zhonghua Lu; Cheng Wang; et al. (Nature Communications)
Abstract Optogenetics is a valuable tool for studying the mechanisms of neurological diseases and is now being developed for therapeutic applications. In rodents and macaques, improved channelrhodopsins have been applied to achieve transcranial optogenetic stimulation. While transcranial photoexcitation of neurons has been achieved, noninvasive optogenetic inhibition for treating hyperexcitability-induced neurological disorders has remained elusive. There is a critical need for effective inhibitory optogenetic tools that are highly light-sensitive and capable of suppressing neuronal activity in deep brain tissue. In this study, we developed a highly sensitive moderately K+-selective channelrhodopsin (HcKCR1-hs) by molecular engineering of the recently discovered Hyphochytrium catenoides kalium (potassium) channelrhodopsin 1. Transcranial activation of HcKCR1-hs significantly prolongs the time to the first seizure, increases survival, and decreases seizure activity in several status epilepticus mouse models. Our approach for transcranial optogenetic inhibition of neural hyperactivity may be adapted for cell type-specific neuromodulation in both basic and preclinical settings.